The Relation between Fasting Blood Glucose and Triglyceride with GFR in Type 2 DM Patients - Hartia, Nabila Putri; Puspitasari, Metana; Sintowati, Retno; Fithriyah, Saidatul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Identify the relation between FBG and triglyceride with GFR in T2DM patients. Methodology: This observational quantitative research used a cross-sectional design. Data were obtained from the medical records of 50 Prolanis T2DM patients in 2023 at the Puskesmas Karangnongko, Klaten Regency, using consecutive sampling technique. The bivariate analysis used was the Spearman test. Results: Spearman test results show that there is no significant relation between FBG with GFR in type 2 diabetes mellitus patients (p-value=0.695; r-value=0.057). Apart from that, there is also no relation between triglycerides with GFR in type 2 diabetes mellitus patients (p-value=0.654; r-value=-0.065). Applications/Originality/Value: This research provides information regarding considerations for FBG and triglycerides as important components for detecting a decrease in GFR which can be an indicator of diabetic nephropathy.